2015
DOI: 10.1159/000381627
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Frequency Range in Japanese and English: The Case of Simultaneous Bilinguals

Abstract: This article reports an experiment to test whether Japanese and English speakers vary their fundamental frequency (f0) range as a function of the language spoken. Speech samples of Japanese-(American) English simultaneous bilinguals (5 males, 5 females; all undergraduates at UC Berkeley) performing comparable reading tasks in their two native languages were analysed. The study builds on a relatively new approach to measuring f0 range that computes its high and low points from tonal targets in the intonational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 50 publications
(51 reference statements)
3
26
4
1
Order By: Relevance
“…Other linguistic and social constraints may also be involved. In the English-Japanese case [29], the authors note a difference in SF0 may be attributable in part to differences in prosodic phonology between the two languages: English has a wide range of available pitch accents while Japanese has only one. Our findings differ in that we find opposite trends across two languages from the same language family (French and Italian), suggesting a reduced importance of this factor.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other linguistic and social constraints may also be involved. In the English-Japanese case [29], the authors note a difference in SF0 may be attributable in part to differences in prosodic phonology between the two languages: English has a wide range of available pitch accents while Japanese has only one. Our findings differ in that we find opposite trends across two languages from the same language family (French and Italian), suggesting a reduced importance of this factor.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of prosody, within-speaker variation for bilinguals by language has also been demonstrated in several cases. Comparing Japanese-English bilinguals, [28] found that women (but not men) use a higher F0 mean in Japanese than in English, and [29] showed bilinguals to exhibit more F0 variability when speaking English than Japanese. [30] found that Welsh-English bilinguals use more F0 variability when speaking Welsh.…”
Section: Introductionmentioning
confidence: 99%
“…Sentences from [7] were used for this project as they were considered to be favourable for pitch analysis, i.e. they contain a high amount of fully voiced segments to avoid F0 discontinuity associated with voiceless segments.…”
Section: Stimulimentioning
confidence: 99%
“…Moreover, the sentences were short enough to typically correspond to a single intonational phrase (IP), enabling to control for declination differences. The study in [7] used 20 sentences, comprising four different types of sentence, namely: A novel component was added to the elicitation procedure, namely addressees' photographs, to account for the effect of formality of the situation reported by Ohara [11]. Three types of addressee were chosen: (1) highly formal-looking addressees, i.e.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation